Novel polyp detection technology for colonoscopy: 3D optical scanner - Refai, Hakki; Koudsi, Badia; Kudsi, Omar Yusef (Endoscopy International Open, 2020)
Background and study aims Fifty-eight percent of American adults aged 50 to 75 undergo colonoscopies. Multiple factors result in missed lesions, at a rate of approximately 20 %, potentially subjecting patients to colorectal cancer. We report on use of a miniaturized optical scanner and accompanying processing software capable of detecting, measuring, and locating polyps with sub-millimeter accuracy, all in real time.Materials and methods A prototype 3 D optical scanner was developed that fits within the dimensions of a standard endoscope. After calibration, the system was evaluated in an ex-vivo porcine colon model, using silicon-made polyps.Results The average distance between two adjacent points in the 3 D point cloud was 94 µm. The results demonstrate high-accuracy measurements and 3 D models while operating at short distances. The scanner detected 6 mm × 3 mm polyps in every trial and identified polyp location with 95-µm accuracy. Registration errors were less than 0.8 % between point clouds based on physical features.Conclusion We demonstrated that a novel 3 D optical scanning system improves the performance of colonoscopy procedures by using a combination of 3 D and 2 D optical scanning and fast, accurate software for extracting data and generating models. Further studies of the system are warranted.